Antioxidant Activity and DPP-IV Inhibitory Effect of Fish Protein Hydrolysates Obtained from High-Pressure Pretreated Mixture of Rainbow Trout (Oncorhynchus mykiss) and Atlantic Salmon (Salmo salar) Rest Raw Material - Elissavet Kotsoni; Egidijus Daukšas; Grete Hansen Aas; Turid Rustad; Brijesh K. Tiwari; Carmen Lammi; Carlotta Bollati; Melissa Fanzaga; Lorenza d’Adduzio; Janne Kristin Stangeland; Janna Cropotova (Marine Drugs, 2024)
The use of fish rest raw material for the production of fish protein hydrolysates (FPH) through enzymatic hydrolysis has received significant interest in recent decades. Peptides derived from fish proteins are known for their enhanced bioactivity which is mainly influenced by their molecular weight. Studies have shown that novel technologies, such as high-pressure processing (HPP), can effectively modify protein structures leading to increased biological activity. This study investigated the effect of various HPP conditions on the molecular weight distribution, antioxidant activity, and dipeptidyl-peptidase IV (DPP-IV) inhibitory effect of FPH derived from a mixture of rainbow trout (Oncorhynchus mykiss) and Atlantic salmon (Salmo salar) rest raw material. Six different treatments were applied to the samples before enzymatic hydrolysis; 200 MPa × 4 min, 200 MPa × 8 min, 400 MPa × 4 min, 400 MPa × 8 min, 600 MPa × 4 min, and 600 MPa × 8 min. The antioxidant and DPP-IV inhibitory effects of the extracted FPH were measured both in vitro and at cellular level utilizing human intestinal Caco-2 cells. The results indicated that low and moderate pressures (200 and 400 MPa) increased the proportion of larger peptides (2–5 kDa) in the obtained FPH, while treatment at 600 MPa × 4 min resulted in a higher proportion of smaller peptides (1–2 kDa). Furthermore, HPP led to the formation of peptides that demonstrated increased antioxidant activity in Caco-2 cells compared to the control, whereas their potential antidiabetic activity remained unaffected.